Exploring dairy heifers’ consistency in social motivation in the absence or presence of conspecifics - Sarah Kappel; Emeline Nogues; Daniel M. Weary; Marina A. G. von Keyserlingk (PLoS ONE, 2025)
Cattle are motivated to maintain social contact, but individual preference for social proximity (i.e., ‘sociability’) varies among individuals. Although personality traits, like sociability, are generally considered to be consistent across context and time, different social environments may elicit different behavioral responses in individuals. We tested individual differences in social motivation with and without the presence of conspecifics, and compared responses within and among different social contexts. Specifically, Holstein heifers (n = 36) were exposed to standardized social isolation tests (novel arena, novel object, runway test; each tested twice, 14 days apart) and a novel social-feed trade-off paradigm. In addition, heifers were subjected to a distribution test in which groups of three animals could freely move between two feed troughs. At one trough, heifers were offered 150 g of grain every two minutes (high side) and every four minutes at the other trough (low side). We expected animals to disperse proportionally to resource availability, corresponding with the Ideal Free Distribution theory (IFD), and that deviations from IFD would reveal individual differences in motivation to be with peers. We found no consistency in sociability measures derived from behaviors in the absence (vocalization, runway latency) and presence (feeding time, social-feed trade-off score) of conspecifics. Moreover, behaviors showed low repeatability within the same social contexts. We conclude that individual differences in sociability are likely context-dependent. We suggest that sociability might not be a single ‘trait’, but rather a ‘behavioral consequence’ resulting from the combined effects of internal characteristics (e.g., other personality traits such as fearfulness) and external factors (e.g., testing environment) at the time of evaluation.